MAKNA SIMBOL DALAM LONDE TORAJA KARYA J.S SANDE KAJIAN SEMIOTIKA C. S. PEIRCE - Balalembang, Werisvo; Faisal, Faisal (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
The purpose of this study is to examine and describe the meaning of symbols contained in the Toraja Londe so that various meanings of symbols contained in the Londe can be known. This type of research is a qualitative descriptive method using Charles S. Peirce's Semiotics as an approach. The results showed that in Londe Toraja there is a convention or the result of community agreement called symbols. Some of the symbols that have been found are related rambu Tuka’, rambu Solo’ dan Aluktodolo.